1992
DOI: 10.1056/nejm199207093270203
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Doses of Calcium-Channel Blockers on Survival in Primary Pulmonary Hypertension

Abstract: This study suggests that high doses of calcium-channel blockers in patients with primary pulmonary hypertension who respond with reductions in pulmonary-artery pressure and pulmonary vascular resistance may improve survival over a five-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
847
1
59

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,415 publications
(926 citation statements)
references
References 20 publications
19
847
1
59
Order By: Relevance
“…30 In another small prospective study, Rich et al showed that patients who did not respond to calcium channel blockers and who were treated with anticoagulants had improved survival as compared with those who were not anticoagulated. 31 …”
Section: Pharmacologic Treatment Anticoagulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In another small prospective study, Rich et al showed that patients who did not respond to calcium channel blockers and who were treated with anticoagulants had improved survival as compared with those who were not anticoagulated. 31 …”
Section: Pharmacologic Treatment Anticoagulantsmentioning
confidence: 99%
“…A decrease of at least 20% in PAP from the baseline value and a decrease of >30% in PVR with an increased or unchanged cardiac output is usually predictive of a favourable response. [31][32][33][34][35] Some workers accept a decrease in mean PAP by >10 mmHg, to a value <40 mmHg with no reduction in cardiac output. 36 Generally only 10-15% of iPAH patients show a positive acute vasoreactive response and about half of them will continue to respond to calcium channel blockers over a long period of time.…”
Section: Vasodilator Challengementioning
confidence: 99%
“…Two small retrospective studies (45,46) reported improved survival with oral anticoagulation in patients with idiopathic PAH. On the basis of these reports and the knowledge that microscopic in situ thrombosis can occur, anticoagulation with warfarin is recommended.…”
Section: General Measuresmentioning
confidence: 99%
“…Patients with idiopathic PAH who respond to vasodilators in the short term have improved survival with longterm use of calcium-channel blockers (46,49). Various short-acting agents, including intravenous epoprostenol or adenosine and inhaled nitric oxide, have been used to test short-term response to vasodilators (50,51).…”
Section: Vasodilator Testing and Calcium-channel Blockersmentioning
confidence: 99%
“…Therapy with high oral doses of calcium-channel blocking agents has been shown to be effective in a selected group of patients (27,28). It has also been shown that continuous intravenous infusion of prostacyclin is beneficial (29)(30)(31)(32)(33).…”
mentioning
confidence: 99%